2017
DOI: 10.1038/s41598-017-08689-1
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation results in liver inflammation and fibrosis in mice infected with Schistosoma japonicum in a Syk-dependent manner

Abstract: Granulomatous and fibrosing inflammation in response to soluble egg antigen (SEA) from Schistosoma japonicum (S. japonicum) is the main pathological process of S. japonicum infection. Inflammasome activation has recently been implicated in the pathogenesis of liver disease. However, the role of inflammasome activation in schistosomiasis-associated liver fibrosis (SSLF) has not been extensively studied. In this study, it is demonstrated that the NLRP3 inflammasome is markedly activated in mouse HSCs both in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…Following this seminal study, NLRP3 inflammasome role has been investigated, especially in S. japonicum infection. In this context, NLRP3 has been shown to be pivotal for inducing hepatic granuloma formation and collagen deposition in the granulomatous structure (18,43). In this study, we confirmed that NLRP3 is pivotal for hepatic granuloma formation, but we did not find any alteration in collagen deposition in Nlrp3 −/− mice when compared to WT (Supplementary Figure S7).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Following this seminal study, NLRP3 inflammasome role has been investigated, especially in S. japonicum infection. In this context, NLRP3 has been shown to be pivotal for inducing hepatic granuloma formation and collagen deposition in the granulomatous structure (18,43). In this study, we confirmed that NLRP3 is pivotal for hepatic granuloma formation, but we did not find any alteration in collagen deposition in Nlrp3 −/− mice when compared to WT (Supplementary Figure S7).…”
Section: Discussionsupporting
confidence: 73%
“…The inflammasome pathway plays an essential role in schistosomiasis-associated liver pathology. It has been demonstrated that NLRP3 is critical for granuloma formation and hepatic stellate cells (HSCs) activation (18) in S. japonicum infections. Regarding S. mansoni infection this same sensor has been shown to be involved in the adaptive immune response and also granuloma formation (9).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has linked NLRP3 inflammasome-driven inflammation to tissue damage and liver fibrosis in conditions such as drug-induced liver injury, alcoholic steatohepatitis (ASH) and angiotensin II (Ang-II) [20, 21]. In fact, recent studies have found that NLRP3 inflammasome is present in liver fibrosis induced by S. japonicum infection [17, 22]. NLRP3 inflammasome is composed of NLRP3 protein, apoptosis associated speck-like protein (ASC) and pro-caspase I [19, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a large number of studies focus on NLRP3 inflammasome expression and its activation mechanisms [35, 36] but few have examined how NLRP3 inflammasome regulates liver fibrosis [7, 22]. Here, we aim to provide more data to deeply understand the effects of NLRP3 on the process of liver fibrosis in schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that Syk-mediated mitogen-activated protein kinases play a vital role in the expression of inflammatory genes [ 31 33 ]. Syk mediates NLRP3 inflammasome activation [ 34 36 ]. Therefore, one can infer that by inhibiting the phosphorylation of Syk, LA inhibits the activity of p38/JNK and reduces both the expression of NLRP3 and the secretion of related proteins IL-1 β and IL-18 ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%